2020
DOI: 10.1002/ejic.201901250
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Hierarchical SAPO‐5 & SAPO‐34 Materials by Post‐Synthetic Alkali Treatment and Their Enhanced Catalytic Activity in Transesterification

Abstract: SAPO‐5 and SAPO‐34 materials were modified using post‐synthetic alkali treatment, which results in the formation of hierarchical SAPO‐5 and SAPO‐34 materials. To test the generation of mesoporosity, the modified materials were thoroughly characterized using XRD, FE‐SEM, TGA, ICP‐OES, and N2 adsorption/desorption techniques. Alkali treated SAPO‐5 and SAPO‐34 materials were utilized for the model reaction triacetin transesterification, under optimized conditions by varying the catalyst amount and reaction time: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Microporous SAPO‐34 material was synthesized using TEAOH (tetraethyl ammonium hydroxide) as template using synthesis procedure available from literature with molar gel composition of 1.0Al 2 O 3 : 1.0P 2 O 5 : 0.6SiO 2 : 1.0SDA : 40H 2 O [46–47] . Aluminum iso‐propoxide (SDFCL, 97 %) and o‐phosphoric acid (Merck, 85 %) were used as sources of aluminum and phosphorous.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Microporous SAPO‐34 material was synthesized using TEAOH (tetraethyl ammonium hydroxide) as template using synthesis procedure available from literature with molar gel composition of 1.0Al 2 O 3 : 1.0P 2 O 5 : 0.6SiO 2 : 1.0SDA : 40H 2 O [46–47] . Aluminum iso‐propoxide (SDFCL, 97 %) and o‐phosphoric acid (Merck, 85 %) were used as sources of aluminum and phosphorous.…”
Section: Methodsmentioning
confidence: 99%
“…Microporous SAPO-34 material was synthesized using TEAOH (tetraethyl ammonium hydroxide) as template using synthesis procedure available from literature with molar gel composition of 1.0Al 2 O 3 : 1.0P 2 O 5 : 0.6SiO 2 : 1.0SDA : 40H 2 O. [46][47] Aluminum iso-propoxide (SDFCL, 97 %) and o-phosphoric acid (Merck, 85 %) were used as sources of aluminum and phosphorous. In a typical procedure, appropriate amount of aluminum iso-propoxide (SDFCL, 97 %) and half of milliQ water was taken in beaker and stirred at the room temperature to form a homogenous mixture.…”
Section: Hydrothermal Synthesis Of Sapo-34mentioning
confidence: 99%
See 2 more Smart Citations
“…Kasyanov et al [101] introduced a novel mesoporous molecular sieve preparation technology, which introduced the surfactant cetyltrimethylammonium bromide in the alkali treatment process, which not only increased the mesoporous ratio, but also the Y-type molecular sieves have high crystallinity and yield. Divya Jadav [102] found that alkali treatment of SAPO materials leads to the formation of mesoporosity with enhanced catalytic activity in the transesterification of triacetin.…”
Section: ) Alkali Treatment Methodsmentioning
confidence: 99%